LITERATUR REVIEW: URGENSI KETERAMPILAN ABAD 21 PADA PESERTA DIDIK - Ina Faizatul Chusna; Irma Nur Aini; Kinanti Amira Putri; Marga Cindy Elisa; Ina Faizatul Chusna; Irma Nur Aini; Kinanti Amira Putri (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
In the era of globalization and rapidly developing technology, education must adapt to the needs of the times. This article reviews the application of 21st century skills in a learning context. 21st century skills, such as creativity, problem solving, collaboration, communication, digital literacy, and critical thinking, are becoming a major focus of modern learning. A learning approach that encourages the development of these skills in a holistic and integrated manner is important in creating a generation that is ready to face future challenges. This article discusses learning strategies and methods that can be used to develop 21st century skills, as well as the challenges that may be faced in their implementation. Through the integration of 21st century skills in the curriculum and innovative learning practices, education can become more relevant and effective in preparing students for success in an ever-changing world. The method used in writing this article is Literature Review. Writing this article started by looking for examples of articles on the research topic being conducted. The criteria for articles used as data are scientific articles sourced from national or international journals with updates in the last 5 years.